2020
DOI: 10.3390/diagnostics10090627
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Microparticles Bearing PF4 and Anti-GAGS Immunoglobulins in Patients with Sepsis

Abstract: PF4 is a megakaryocyte-derived cationic chemokine that plays a part in innate immunity through its activity on the macrophages. In bacterial sepsis, PF4 binds to glycosaminoglycans (GAGs) on the surface of aerobic bacteria, giving rise to an antigenic complex that induces the early formation of anti-PF4 IgG-IgA-IgM. This triggers the immune response in patients receiving heparin therapy who develop heparin-induced thrombocytopenia (HIT). These antibodies have also been identified in patients with chronic Gram-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…As reported, PLT plays an important role in hemostasis and the protection against bacterial infection. 22 Platelets have a direct antibacterial defense effect by recognizing microbial antigens and secreting antimicrobial peptides and kinocidins, enhancing innate immune effectors (including complement, neutrophils) and adaptive coordinate immunity (APS, T cells, and B cells). 23 However, in our study, PLT levels decreased in the blood culture-positive group compared with the blood culture-negative group with an AUC of 0.5803 to differentiate these two groups, and the specificity was too low, which needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, PLT plays an important role in hemostasis and the protection against bacterial infection. 22 Platelets have a direct antibacterial defense effect by recognizing microbial antigens and secreting antimicrobial peptides and kinocidins, enhancing innate immune effectors (including complement, neutrophils) and adaptive coordinate immunity (APS, T cells, and B cells). 23 However, in our study, PLT levels decreased in the blood culture-positive group compared with the blood culture-negative group with an AUC of 0.5803 to differentiate these two groups, and the specificity was too low, which needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…One group presented a case of thrombocytopenia in the setting of heparin exposure and bacteremia with methicillin-susceptible Staphylococcus aureus, arguing that the bacteremia may have contributed to the clinical picture of HIT [79]. Sartori et al [80] found somewhat increased levels of anti-PF4/PVS antibodies in septic patients versus controls, although there was no difference in IgGspecific antibodies.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Alternative methods for measurement of platelet activation in human patients with systemic inflammatory diseases (i.e., sepsis, SIRS, MODS) include whole blood impedance aggregometry (multiplate analyzer), 1,17 measurement of soluble forms of platelet membrane glycoproteins (i.e., sPselectin and sCD40L) with ELISAs, 11,18,19,40,51 and also using ELISA measurements of platelet-specific molecules released from platelet granules during activation (i.e., platelet factor 4, microparticles, microparticle-associated tissue factor, βthromboglobulin). 41,52,58,69 Whole blood impedance aggregometry (multiplate analyzer) is a point-of-care test and was evaluated in the same cohort of equids as our study, but there were no significant differences in aggregation values between SIRS cases and controls. 21 Similarly, the soluble form of glycoproteins CD40L and CD62P could not be quantified in equine plasma samples using commercial human ELISAs.…”
Section: Discussionmentioning
confidence: 77%